Pacifism’s Appeal
XIII, 247 p. 4 illus., 1 illus. in color.
Keywords: Jorg Kustermans teaches international politics in the Department of Political Science at the University of Antwerp, Belgium. His scholarship is situated at the intersection of international theory and social theory and has dealt with such questions as state personhood, republican security, the nature of social practices, and the relation of boredom and war. Tom Sauer is Associate Professor in International Politics at the Universiteit Antwerpen, Belgium. He is co-editor of Nuclear Terrorism: Countering the Threat, and author of Eliminating Nuclear Weapons: The Role of Missile Defense and Nuclear Inertia: US Nuclear Weapons Policy after the Cold War. Dominiek Lootens is Deputy Academic Director at University Centre Saint Ignatius Antwerp, Belgium, Vice-President Society for Intercultural Pastoral Care and Counselling, International Advisor International Thomas Merton Society, and Co-Editor of Where Are We? Pastoral Environments and Care for Migrants: Intercultural and Interreligious Perspectives. Barbara Segaert is scientific coordinator at the University Centre Saint-Ignatius Antwerp, Belgium, where she develops academic programmes on various topics of contemporary relevance to society. She was co-editor of Genocides: an Interdisciplinary Approach to Risk and Resilience. This volume examines the possibility – or need – of a revitalization of pacifism as a world-political practice. It takes as its point of departure the observation that although ‘just war thinking’ has long been dominant in Western debates about war and peace, recent events have served to temper enthusiasm about the doctrine. Pacifism has been much less prominent a stance in recent decades, but there is the impression that it may be staging a return. Just war thinking has to a large extent failed. Outright bellicism remains as undesirable as ever. Pacifismpresents itself again as a possible alternative. Once upon a time the peace movement was popular, and pacifism with it. Pacifism appealed to people. It stirred hearts and minds. It inspired political action and institutional designs. This volume examines whether pacifism can claim its ground again and how it should be redefined in light of today’s world-political circumstances.